(3ebGeI GdeaGNQI Hjf GdSja hGdbdes - (3CMeO Hf eMeO Hf CMeO Hf HQO GdCfOdSj, CHh MaU,J (B440 (3g` s
(3ChdgG (B:s
(3CXgQ ai GdeZGjQI HjfgG GdTjN LeGd GdOjf , eGUOb Hg bhdg GdbGFd hEfi (B[(3hEf(B] (3cfJ GdCNjQ ReGfg dBJ HeG de JSJWYg GdChGFd s
(3BNQgG (B:s
(3hjeJY HXdGd ebGeI GdPi dGJcSQ GdCjGe ebOGQ eGgh LGHQ, dGJLHQ eGgh cGSQ , Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cGf MjkG SfI (B440 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(D1042) s
Keywords: (3GdCOHs